Perpaduan Asesmen Kinerja dengan Google Meet dalam Mendorong Hasil Belajar IPA Siswa - I Wayan Eka Mahendra; Ni Nyoman Parmithi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve science learning outcomes for students of class X SMK Kesehatan Sanjiwani, Gianyar during the online learning period through a combination of performance assessment and Google Meet. The method used is a quasi-experimental design with a non-equivalent control group design, involving a sample of 58 people taken by simple random sampling. The results showed that students who took online learning using a combination of performance assessment and Google Meet were better than the science learning outcomes of students who took online learning without a variety of performance assessment and Google Meet. In conclusion, there is an effect of the application of performance assessment and Google Meet on the science learning outcomes of class X students of SMK Kesehatan Sanjiwani, Gianyar. Keywords: Performance Assessment, Google Meet, Learning Outcomes